Nilotinib Significantly Induces Apoptosis in Imatinib Resistant K562 Cells, as Effectively as in Parental Sensitive Counterparts - Baran, Yusuf; Ekiz, Hüseyin Atakan; Can, Geylani; Baran, Yusuf; Ekiz, Hüseyin Atakan (Ferrata Storti Foundation, 2009)
[No abstract available]
14th Annual Meeting of the European-Hematology-Association